Expert Systems: Principles and Programming - Giarratano (Joseph); Riley (Gary) (2007)
Expert System
44051a.jpg;44051b.jpg;44051c.jpg;44051d.jpg;44051e.jpg;44051f.jpg;44051g.jpg
22.5
Keywords: Expert System